Perancangan Dokumen Hazard Identification, Risk Assessment and Risk Control (HIRARC) di PT. Cahaya Citra Alumindo - Yosephine Gabriela; Kriswanto Widiawan (Jurnal Titra, 2020)
PT. Cahaya Citra Alumindo is a manufacturing company that produce alloy wheels for car and golf cart. Based on interview, company work’s accident are 3-4 minor accidents every month and 1-2 major accidents every year. The goal of HIRARC is to help the company to detect hazard in work’s activity, risk assessment and documenting risk control for worker’s safety and health. HIRARC is based on ISO 45001:2018 and goverment regulations No. 5/2012 about Management System Occupational Health and Safety (SMK3) as the early stage to implement SMK3. The results of HIRARC shows that there are still many activities that endangers worker. There are 30% activities classified as moderate risk, 17% as significant risk and 18% as high risk. Continued by risk control which goal is to minimize risk by elimination, substitution, engineering controlm administrative control and PPE. The estimation of decreased risk rating posibility if risk controls implemented are 15% as moderate risk, 2% as significant risk and 0% as high risk.